A Social Life Of Malabar Coast With Special Reference To Maritime Contacts - C K, Shamli; Sabna K, Sabna K (Journal of Neonatal Surgery, 2025)
The Malabar Coast, situated along the south-western littoral of the Indian subcontinent, has historically occupied a significant position in the maritime history of the Indian Ocean world. As a region shaped by long-standing interactions between land and sea, Malabar emerged as a vibrant zone of commerce, cultural exchange, and social transformation. This study examines the social dimensions of maritime life on the Malabar Coast, with particular emphasis on the role of ships, fishing communities, trade networks, and coastal settlements in shaping regional society. Drawing upon literary sources, archaeological findings, travellers’ accounts, and ethnographic evidence, the research explores the ways in which maritime activities influenced patterns of economic organization, social relations, legal practices, and cultural expressions. The study argues that the sea functioned not merely as a medium of transportation and trade but as a dynamic social space that facilitated the movement of people, goods, ideas, and beliefs across geographical boundaries. By foregrounding the experiences of maritime communities and their interactions with wider commercial networks, the research highlights the centrality of the maritime sphere in the historical development of Malabar. In doing so, it contributes to a deeper understanding of the interconnected relationship between coastal environments, human societies, and the broader processes of social and cultural change in the Indian Ocean region.....